2021
DOI: 10.1186/s12903-021-01681-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of caries experience and the impact on the OHRQOL of 6-year-old Libyan children: a cross-sectional survey

Abstract: Objective The current study aimed to assess the caries experience and associated factors and its impact on the oral health-related quality of life (OHRQoL) among 6-year-old Libyan children. Methods A cross-sectional survey including 706 six-year-old children was conducted in 2017 in Benghazi, Libya. Data were collected through a self-administered questionnaire assessing socioeconomic status and oral health behaviours, and the Arabic version of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
0
6
2
Order By: Relevance
“…Our data (86.6%) was higher than that found in previous studies conducted on Libyan children, 42.22%, 63.5%, 50%, 58%, 57.8%, 77.72% 49.0%, 55.8%, 74.7% [3,[10][11][12][13][14][15][16][17], respectively. Moreover, our data was higher than figures reported in more recent Libyan studies 45%, 71%, 78% [18][19][20], respectively. Therefore, the trend of dental caries in Libya has shown noticeable increase since the previous studies conducted in 1991 (42.22%) [3] to the figure in 2021 (78%) [20] up to our data in the present study (86.6%).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our data (86.6%) was higher than that found in previous studies conducted on Libyan children, 42.22%, 63.5%, 50%, 58%, 57.8%, 77.72% 49.0%, 55.8%, 74.7% [3,[10][11][12][13][14][15][16][17], respectively. Moreover, our data was higher than figures reported in more recent Libyan studies 45%, 71%, 78% [18][19][20], respectively. Therefore, the trend of dental caries in Libya has shown noticeable increase since the previous studies conducted in 1991 (42.22%) [3] to the figure in 2021 (78%) [20] up to our data in the present study (86.6%).…”
Section: Discussioncontrasting
confidence: 93%
“…Other previous Libyan studies showed lower figures of mean dmft; 2.32 [10], 2.58 [12], 2.0 [15], 2.32 [13] and 2.72 [17]. But higher figure was found in recent studies in Libya, 3.23 [19], and 3.7 [20]. The mean dmft of the present study was in disagreement with that found in other studies conducted in other developing countries; higher than that found in Karachi (2.01) [24], in Syria (2.47) [26], in China (2.21) [38], but lower than that found in Egypt (3.23) [25], in Saudi Arabia (3.66) [39].…”
Section: Discussionmentioning
confidence: 75%
“…Contrarily, maternal employment status was considered to be a potential socioeconomic indicator for OHRQoL in Generation R Cohort. In Ballo et al's study, children from higher income families had low OHRQoL impacts compared to their peers from lower socio-economic status (28). This is best explained by the effect of material deprivation on lifestyle and diet among poorer families.…”
Section: Discussionmentioning
confidence: 94%
“…Dental treatment under general anesthesia is a feasible option for uncooperative children, and this mode of administration will provide a single-visit solution for such children. 27 A Brazilian study 28 reported a negative association between child caries experience and quality of life (Brazilian ECOHIS, B-ECOHIS) among the mothers. Similar findings were evident with the present study, which compared foundling and delinquent children with mainstream children; however, the results were not comparable.…”
Section: Resultsmentioning
confidence: 99%